Ekoliterasi Peserta Didik Melalui Kegiatan Recycle: Pelatihan dan Pengelolaan Sampah Anorganik - Irhas, Muhammad; Anhar, Nurfadilah; Rasid, Ratnawati; Asis, Amaliah Arfina; Syamsul; Jamilah (Faculty of Tarbiyah and Teacher Training, 2025)
Looking at the problems experienced in the world of education, ecoliteracy is one of the many problems. Lack of understanding and awareness to keep the environment healthy and clean. This must be followed up by conducting research which aims to provide students with an understanding of the importance of ecoliteracy through Recycling activities in the form of training and inorganic waste management. The results obtained from this research show that the activities carried out can produce positive results for the environment and students. Where students can hone their creativity and the environment can be followed up so that it remains maintained.